PELATIHAN KETERAMPILAN PSIKOLOGIS MODEL BK âPROAKTIFâ UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH PADA GURU SD - , Hanifa Laura Dalimunthe, Dr. Nuryati Atamimi, SU., Psi. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Homeroom teachers in primary schools should do their overall tasks like deliver course materials and give guidances and counseling services to all students. Homeroom teachers are often faced with problems of students in the classroom, but teacher skill to solve their problems still inadequate. To give an optimal services, homeroom teachers should have the students' problem-solving skills. One of the training that has proven to improve psychological skills and able to optimize the function of guidances and counseling is the training model of BK \"PROAKTIF\". This study aims to test the effectiveness of the training model of BK \"PROAKTIF\" in improving problem-solving skills in hoomeroom teachers in primary schools with variable self efficacy as manipulation chek. Design that will be used is a quasi experimental design with untreated control group design with pre-test and post-test. A total of 16 teachers will be put in the experimental group and 16 in the control group. The research instrument that will be used is test of problem-solving skills and self efficacyâscale. Technique data analysis used is Mixed Anava.The results is increase problem-solving skills in homeroom teachers, the experimental group is higher scores compared to controls.